2000
DOI: 10.1021/ja9925397
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Relative Ordering of Activation Energies for Gas-Phase Ion Unimolecular Dissociation by Infrared Radiation for Gaseous Multiphoton Energy Transfer

Abstract: We report the use of a continuous-wave (CW) CO2 laser for the determination of relative activation energy for unimolecular dissociation of large biomolecular ions. The [M + 5H]5+ and [M + 11H]11+ ions of bovine ubiquitin and the [M + H]+ ion of bradykinin are irradiated with a CW CO2 laser and the rate constant for dissociation at each of several laser intensities recorded. A plot of the natural logarithm of the first-order rate constant versus the natural logarithm of laser intensity yields a straight line wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 71 publications
4
69
0
3
Order By: Relevance
“…There is an excellent agreement between master equation modeling (open symbols) and the blackbody curve (line). There is a slight deviation between the actual IED for (Ala-Gly) 8 ions excited by cw laser (dashed line) and blackbody irradiation (solid line) as shown in Figure 16 (Freitas, Hendrickson, & Marshall, 2000).…”
Section: Internal Energy Distributionmentioning
confidence: 98%
See 2 more Smart Citations
“…There is an excellent agreement between master equation modeling (open symbols) and the blackbody curve (line). There is a slight deviation between the actual IED for (Ala-Gly) 8 ions excited by cw laser (dashed line) and blackbody irradiation (solid line) as shown in Figure 16 (Freitas, Hendrickson, & Marshall, 2000).…”
Section: Internal Energy Distributionmentioning
confidence: 98%
“…This correction decreases rapidly with increase in the size of the molecule and is expected to be negligibly small for large molecules. For example, Marshall and co-workers found that for (AlaGly) 8 H þ there is an almost perfect overlap between the IEDs of ions with and without dissociation (Freitas, Hendrickson, & Marshall, 2000), implying that the reactive depletion correction for this size system is close to zero. The corresponding correction for excited n-butylbenzene ions is 0.05 eV (Uechi & Dunbar, 1992).…”
Section: Kinetics Of Irmpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, IRMPD can be used for the determination of the activation energy, E a , for gas-phase unimolecular dissociation reactions. This approach was first introduced for small molecules (Ͻ50 atoms) by Dunbar [38,39], and later extended to large biomolecules (Ͼ50 atoms) by Marshall and coworkers [40,41]. These authors renamed the technique as focused radiation for gaseous multiphoton energy-transfer (FRAGMENT).…”
mentioning
confidence: 99%
“…In addition, to study the effect of Fe(III) binding on the unimolecular kinetics and relative activation energies for the dissociation of enterobactin in the gas phase, time-resolved IRMPD experiments were carried out on ent and ent-Fe(III). The FRAGMENT method [40,41]üwasüemployedüto determine relative dissociation energetics.…”
mentioning
confidence: 99%